Is There an Association between Being a Victim of Physical Violence by Intimate Partner and Binge Drinking in Men and Women? Secondary Analysis of a National Study, Peru 2020 - Campoverde, Francesca (2022)
The relationship between being a victim of physical violence by an intimate partner and binge drinking (BD) is a poorly explored line of research, especially in men. To determine the association between being a victim of physical violence by an intimate partner and BD in men and women in Peru in 2020, a secondary analytical cross-sectional study was conducted using the Demographic Health Survey. BD was categorized according to the Center of Disease Control definition for men and women, based on the type and amount of alcoholic beverage ingested. Physical violence was based the report of being hit with any part of the body or an object, by their intimate partner. To identify the association, a multivariable general linear model of the family and link log Poisson was used. The results were presented as prevalence ratios (PRs). In the adjusted models stratified by sex, a 90% greater likelihood of BD was found in male victims and an 80% higher probability among female victims (PRa 1.9, 95%CI 1.3;2.7, p < 0.001 vs. PRa 1.8, CI95% 1.1; 2.8, p = 0.013, respectively). An association was found between physical violence by an intimate partner and BD in the Peruvian population older than 15 years, in both men and women.